MCM9 compound heterozygosity in an adolescent with premature ovarian insufficiency - Elise Nauwynck; Michel De Vos; Alexander Gheldof; Bart JH Dequeker; Annelore Van Der Kelen; Frederik Hes; Stephanie Verheyden; Jesse Vanbesien; Inge Gies; Jean De Schepper; Willem Staels (Endocrinology, Diabetes & Metabolism Case Reports)
Delayed puberty in girls is often related to late maturation but is occasionally the first sign of premature ovarian insufficiency (POI). POI is a condition that affects ovarian function and fertility, and its etiology is unknown in most cases. Genetic factors have recently been identified in 20–25% of women with POI, involving genes that regulate various aspects of ovarian development and maintenance. We report a case of delayed puberty due to POI in an adolescent from a non-consanguineous family who carried two variants in the MCM9 gene. MCM9 is essential for DNA replication and repair, and its dysfunction can lead to chromosomal instability and ovarian failure. Our case highlights the importance of targeted gene panel analysis, particularly in POI patients with negative autoimmunity screening, and evidence of ovarian or uterine dysgenesis on pelvic imaging.